Bulk growth and an efficient mid-IR laser of high-quality Er:YSGG crystals. Issue 12 (27th February 2019) - Hu, Qiangqiang; Nie, Hongkun; Mu, Wenxiang; Yin, Yanru; Zhang, Jian; Zhang, Baitao; He, Jingliang; Jia, Zhitai; Tao, Xutang
Abstract : This work reports on the growth of the high quality large size Er:YSGG crystals and their highly efficient 2.8 nm laser. Abstract : Herein, bulk single crystals of Er:Y3 Sc2 Ga3 O12 (Er:YSGG) with a maximum diameter of 35 mm or a maximum length of 100 mm were successfully grown by the Czochralski method using a 60 mm diameter crucible. The high-resolution X-ray diffraction and optical interferometry results indicated that the as-grown crystals were of high quality. The crystalline perfection of the as-grown crystal was evaluated to be 20.58′′ via the FWHM of the rocking curve, and the optical homogeneity RMS was in the order of 10 −6 . A continuous wave laser of the Er:YSGG crystal operating at 2798.7 nm has been demonstrated. Moreover, a maximum output power of 745 mW has been realized. The achieved maximum slope efficiency is 31.5%, which is, to date, the highest slope efficiency in the Er:YSGG crystal lasers operating at ∼2.8 μm.